Development: History and Power of the Concept. Issue 1 (2nd January 2020) - Koponen, Juhani
Abstract: This article provides an alternative reading of the history of development by tracing how the concept of development has accumulated its present power. It starts from the premise that whatever development is, it is also a concept which is deeply ingrained in our 'Western' habitus and can inform and guide our actions. Contrary to suggestions that it was 'invented' once – at whatever date – and then spread elsewhere, I argue that it emerged gradually by being born and reborn several times in different contexts. Thus, its history is not of direct genealogical continuities from a single origin but rather of parallels generated by similar structural circumstances. Although development is commonly criticised for its ambiguity, I argue that much of its power actually stems from its linguistic polyvalence: its different meanings make it useful for many different purposes. Yet the concept is held together by a more coherent structural frame which combines three main senses: ideal, processual and intentional. Building on research on colonial history, I locate a birth of development in European colonialism, where it worked as an unacknowledged condition of colonial exploitation. It also has other antecedents that remain insufficiently understood. Having been introduced in the South as a notion for colonial exploitation of local resources, after World War II its function changed again. At the dissolution of the colonial empires, it was taken into its present use as soft power by Western powers and anti-colonial nationalists alike and was transformed into the foundational concept of developmentalism. But its power has limits. Ultimately, while concepts can and do affect people's behaviour, they work within the dynamics of material and mental interests.